Hepatotoxic effects of aristolochic acid: mechanisms and implications - Zhang, Qian; Chen, Jiayun; He, Hengkai; Zhao, Wentong; Wong, Yinkwan; Li, Wenhui; Feng, Sha; Liu, Bin; Wang, Jigang; Luo, Piao (Acta Materia Medica, 2024)
Herbal plants that contain aristolochic acids (AAs) have been widely used for medicinal purposes for centuries. However, human exposure to AAs via herbal or dietary intake is thought to be a causative factor for aristolochic acid nephropathy (AAN), hepatotoxic effects, and carcinomas. At present, the molecular mechanisms underlying AA-induced hepatotoxicity and carcinogenesis and the corresponding detoxification strategies are unclear. This review summarizes the exposure, absorption, distribution, metabolism, and excretion (ADME) process of AAs. Importantly, to more objectively determine the emerging correlation between AAs and liver cancer, this review summarizes the possible direct and indirect connections between AAs and liver cancer. In brief, this review comprehensively summarizes and analyzes the molecular mechanisms underlying AA-induced hepatotoxicity and carcinogenesis, as well as an assessment of current detoxification strategies. At the same time, a new view on the prevention and detoxification of AA-induced hepatotoxicity is proposed. Chinese medicines that contain AAs might induce liver cancer but this is a controversial notion. This review summarizes relevant views from the past and provides novel insight into AA-induced liver injury or cancer to lay the foundation for AA detoxification.